Nose to brain delivery of selegiline loaded PLGA/lipid nanoparticles : Synthesis, characterisation and brain pharmacokinetics evaluation - Raman, Subashini; Khan, Arshad Ali; Mahmood, Syed (Editions de Sante, 2022)
Parkinson's disease (PD) is the second most common progressive neurodegenerative disease that promotes neuronal cell death. The primary treatment strategy for Parkinson's disease involves the therapy of an MAO-B inhibitor molecule, selegiline. The present research aims to fabricate selegiline loaded polymeric (PLGA) nanoparticles (SPNPs) and selegiline loaded lipid-PLGA hybrid nanoparticles (SLPNPs) while using the single emulsion solvent evaporation method. The prepared SPNPs and SLPNPs formulations were subjected to preliminary optimisation using particle size, zeta-potential, and entrapment efficiency (EE%), and the selected formulations were subjected to further characterisation. Scanning electron microscopy (SEM) and high-resolution transmission electron microscopy (HRTEM) confirmed the particles' 2-D spherical morphology and size. ATR-FTIR was used to evaluate the physical interactions among the formulation ingredients. Differential scanning calorimetry (DSC) and X-ray diffraction (XRD) studies confirm that SPNPs and SLPNPs were in an amorphous state. Ex-vivo studies showed 77.56% and 80% of drug permeation in 24 h for optimised formulations of SPNPs-2 and SLPNPs-1, respectively, while pure selegiline showed 65% Permeation. In-vivo study revealed a steady and controlled release profile with a half-life of 13.5 h, and AUC0-24 was observed at 130327.56 ± 231.6 ng/ml*h for SPNPs-2. For SLPNPs-1 an immediate release was observed with a very short half-life and AUC0-24 47548.57 ± 434.8 ng/ml*h compared with pure selegiline HCl solution with 2.3 h and AUC0-24 11116.52 ± 345.7 ng/ml*h. SLPNPs-1 has a shorter half-life due to its immediate release properties with the presence of lipid. Meanwhile, SPNPs-2, which only has a polymeric layer, has a longer half-life due to its sustained release properties. Overall, SPNPs-2 and SLPNPs-1 are promising carriers for selegiline nasal uptake and increase its brain bioavailability compared to oral absorption by pure selegiline.